Living a normal life in an extraordinary way: A systematic review investigating experiences of families of young people's transition into adulthood when affected by a genetic and chronic childhood condition. (October 2016) - Waldboth, Veronika; Patch, Christine; Mahrer-Imhof, Romy; Metcalfe, Alison
Abstract: Introduction: The transition into adulthood is a developmental stage within the life cycle. A chronic childhood condition can disrupt this transition and create major challenges for both the young person and his or her family. Little is known about families' experiences when living with a rare genetic disease. Therefore, the purpose of this literature review was to understand experiences of families living with a chronic childhood disease during transition into adulthood by integrating evidence. Method: A systematic review using an integrative approach to data inclusion and analysis comprising qualitative, quantitative and other methodological studies about a range of genetic and chronic childhood diseases was undertaken to identify relevant information. Databases searched were PubMed, Cochrane Library, PsychINFO, CINAHL, and AMED, using the search terms (1) family, caregivers, young adult, adolescent; (2) adolescent development, transitional programs, transition to adult care; (3) muscular dystrophy, spinal muscular atrophy, cystic fibrosis, haemophilia and sickle cell disease. Study findings were critically appraised and analyzed using critical interpretive synthesis. Results: A total of 8116 citations were retrieved. 33 studies remained following the removal of duplicates, papers unrelated to genetic childhood conditions and families' experiences of the transition into adulthood. Findings provided three perspectives: (1) the young person's perspective on how to "live a normal life in an extraordinary way" and "manage a chronic and life threatening disease"; (2) the parent perspective on the "complexity of being a parent of a chronically ill child" and "concerns about the child's future" and (3) the sibling perspective on "concerns about the siblings future". As a consequence of the genetic childhood condition, during the ill family members' transition into adulthood all family members were at risk for psychosocial difficulties as they mutually influenced each other. Previous research focused predominately on the individual illness experience, and less emphasis was put on the family perspective. Conclusions: Young people and their family members experienced multiple challenges and not only for the ill individual but also there were consequences and health risks for the whole family system. Therefore, a family systems perspective to research and care is indicated to assist affected families to cope with their complex life and health situation.